A nylon 66 composite material and its preparation method and application
By combining a specific composition of a synergistic flame retardant with halogen-free flame retardant, flat glass fiber and specific viscosity nylon 66, the problem of insufficient laser transmittance and easy precipitation under high temperature and high humidity conditions during laser welding is solved, and high laser transmittance and excellent flame retardant performance are achieved, and stable under high temperature and high humidity conditions are achieved.
Patent Information
- Application Number
- CN202311673500.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-12-07
AI Technical Summary
The existing halogen-free flame-retardant nylon 66 materials have defects such as insufficient laser transmittance, easy decomposition, and lead to smoke and bubbles during laser welding, and are easy to precipitate under high temperature and high humidity conditions, which limits its application.
By combining a specific composition of a synergistic flame retardant with halogen-free flame retardant (inorganic hypophosphite), flat glass fiber and specific viscosity nylon 66 66, the material has high laser transmittance and excellent flame retardant properties, and is stable under high temperature and high humidity conditions.
It realizes the efficient application of nylon 66 composite materials in laser welding process, has high laser transmittance, excellent flame retardant performance and stability under high temperature and high humidity conditions, avoiding the problems of lower laser transmittance and easy precipitation caused by traditional flame retardants.
Smart Images

Figure BDA0004594038120000091 
Figure BDA0004594038120000101 
Figure BDA0004594038120000102
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified nylon composite materials, and specifically relates to a nylon 66 composite material and a preparation method and application thereof. Background Art
[0002] The concept of laser welding began in the 1970s. It usually uses a diode laser or a neodymium-doped yttrium aluminum garnet (Nd:YAG) laser with a wavelength between 700-1200nm to generate a large amount of heat at the welding site, thereby melting the contact area of the components to form a welding site.
[0003] Compared with traditional plastic welding processes, laser welding can be applied to various flexible structures. It has high welding strength, and its fast heating and cooling rates can reduce the thermal impact on the material. It does not produce external forces on the weldment, so the stress and deformation of the weldment are very small. In addition, the laser welding process is stable, and the surface and internal quality of the weld are very good. It can be welded in vacuum, air or other gas environments, and has low requirements for the welding medium. It can also be welded through glass or other materials that are transparent to the light beam. Due to the above unique advantages of laser welding, it has been successfully applied to the precision welding of micro-small parts.
[0004] The repeating units on the nylon 66 (PA66) molecular chain contain polar amide groups, which can form hydrogen bonds between molecules, have a regular structure, are crystalline, and have strong intermolecular interaction forces. Therefore, the main characteristics of polyamide are excellent mechanical properties, high strength, high rigidity, and good toughness; they have self-lubrication and good friction resistance; they have a wide operating temperature range, good electrical insulation properties, high volume resistivity and breakdown voltage, and good oil resistance and chemical stability. With the development of new energy vehicles, halogen-free flame-retardant nylon is widely used in high-voltage connectors, charging gun plugs and sockets, actuator housings and other electronic and electrical components due to its good electrical insulation properties, flame retardant properties, excellent toughness and high CTI values. However, since the amide groups in the PA66 molecular chain can easily form hydrogen bonds with water molecules, it has the disadvantage of high water absorption. In addition, in the prior art, halogen-free flame-retardant nylon, the flame retardant is generally melamine polyphosphate (MPP), melamine cyanuric acid (MCA) or orthophosphate and organic hypophosphite compounded to improve the flame retardant properties of the material; however, this type of material is not suitable for laser welding technology, and has defects such as insufficient laser transmittance during laser welding, easy decomposition resulting in a large amount of smoke and blistering, and easy precipitation after high temperature and high humidity; and the laser transmittance of black nylon material in the prior art is low, thus limiting the application of halogen-free flame-retardant nylon material.
[0005] Therefore, developing a nylon 66 material that has both high laser transmittance and excellent flame retardant properties, has no precipitation under high temperature and high humidity conditions, and is suitable for laser welding technology is an urgent problem to be solved in this field. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a nylon 66 composite material and its preparation method and application. The nylon 66 composite material, through compounding of various components, has the advantages of high laser transmittance, good flame retardancy and less precipitation under high temperature and high humidity conditions, and is particularly suitable for electronic components prepared by laser welding process.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a nylon 66 composite material, which comprises, by weight, 25 to 62 parts of nylon 66 resin, 13 to 54 parts of flat glass fiber, 10 to 20 parts of halogen-free flame retardant and 5.5 to 10 parts of synergistic flame retardant; the halogen-free flame retardant is an inorganic hypophosphite; the synergistic flame retardant comprises a combination of non-cage polysiloxane and cage polysilsesquioxane; and the viscosity of the nylon 66 resin is less than or equal to 3.0.
[0009] In the present invention, a synergistic flame retardant of a specific composition is compounded with a specific type of halogen-free flame retardant, flat glass fiber and nylon 66 of a specific viscosity, so that the nylon 66 composite material can have both high laser transmittance and excellent flame retardant properties, and is resistant to high temperature and high humidity, has no precipitation after long-term treatment under high temperature and high humidity, and has good stability; it avoids the disadvantages of decreased laser transmittance and easy precipitation caused by the use of other compound flame retardants, and is particularly suitable for products prepared by laser welding technology.
[0010] In the present invention, the nylon 66 resin is 25 to 62 parts, for example, it can be 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 33.5 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 50.5 parts, 51 parts, 51.5 parts, 52 parts, 52.5 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, etc.
[0011] The flat glass fibers may include 13 to 54 parts, for example, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, etc.
[0012] The halogen-free flame retardant can be 10 to 20 parts, for example, it can be 10 parts, 10.2 parts, 10.5 parts, 10.8 parts, 11 parts, 11.2 parts, 11.5 parts, 11.8 parts, 12 parts, 12.2 parts, 12.5 parts, 12.8 parts, 13 parts, 13.2 parts, 13.5 parts, 13.8 parts, 14 parts, 14.2 parts, 14.5 parts, 14.8 parts, 15 parts, 15.2 parts, 15.5 parts, 15.8 parts, 16 parts, 16.2 parts, 16.5 parts, 16.8 parts, 17 parts, 17.2 parts, 17.5 parts, 17.8 parts, 18 parts, 18.2 parts, 18.5 parts, 18.8 parts, 19 parts, 19.2 parts, 19.5 parts, 19.8 parts, 20 parts, etc.
[0013] The synergistic flame retardant is 5.5 to 10 parts, for example, it can be 5.5 parts, 5.8 parts, 6 parts, 6.2 parts, 6.5 parts, 6.8 parts, 7 parts, 7.2 parts, 7.5 parts, 7.8 parts, 8 parts, 8.2 parts, 8.5 parts, 8.8 parts, 9 parts, 9.2 parts, 9.5 parts, 9.8 parts, 10 parts, etc.
[0014] Preferably, the viscosity of the nylon 66 resin is less than or equal to 3.0, for example, it can be 1, 1.2, 1.5, 1.8, 2, 2.2, 2.4, 2.42, 2.44, 2.46, 2.48, 2.5, 2.52, 2.54, 2.56, 2.58, 2.6, 2.62, 2.64, 2.68, 2.7, 2.72, 2.74, 2.76, 2.78, 2.8, 3, etc.; preferably, it is 2.4-2.8.
[0015] In the present invention, the viscosity of the nylon 66 resin is tested according to the FZ / T51004-2011 standard.
[0016] In the present invention, the resin viscosity of nylon 66 is not within the above-defined range, the viscosity is high, and the processing performance is poor.
[0017] Preferably, the diameter of the short side monofilament of the flat glass fiber is 6 to 15 μm, for example, it can be 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.
[0018] Preferably, the average profile ratio of the flat glass fibers is 3 to 5, for example, 3, 3.5, 4, 4.5, 5, etc.
[0019] Preferably, the inorganic hypophosphite includes at least one of inorganic aluminum hypophosphite, inorganic zinc hypophosphite, and inorganic calcium hypophosphite, and preferably the inorganic hypophosphite is inorganic aluminum hypophosphite.
[0020] Preferably, the mass ratio of the non-cage polysiloxane to the cage polysilsesquioxane is 1:(0.1-5.5), wherein the specific value in (0.1-5.5) can be, for example, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5, etc.; more preferably, it is 1:(1-4).
[0021] In the present invention, the mass ratio of the non-cage polysiloxane to the cage polysilsesquioxane is not within the above-defined range. When the amount of the cage polysilsesquioxane is too small, the flame retardancy of the composition is affected; when the amount of the cage polysilsesquioxane is too large, the transmittance of the composition is affected.
[0022] Preferably, the cage-type polysilsesquioxane comprises dodecaphenyl cage-type polysilsesquioxane and / or octaphenyl cage-type polysilsesquioxane.
[0023] Preferably, the non-cage polysiloxane includes any one of branched polysiloxane, linear polysiloxane or branched phenyl silicone oil.
[0024] Preferably, the nylon 66 composite material further includes 0.05 to 1.2 parts of colorant by weight, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, etc.
[0025] Preferably, the colorant includes at least one of linear quinacridone red, naphthoxycyclopentane red, complex red, azo orange, azo complex yellow, perylene yellow, anthraquinone violet, anthraquinone blue, methylene orange, phthalocyanine blue, azo orange or phthalocyanine green.
[0026] In the present invention, the nylon 66 composite material can be natural color, or different colorants can be added to obtain composite materials of different colors; different colorants can also be compounded to obtain a black nylon composite material; and for the black nylon composite material, the black colorant formed by colorants of different colors used in the present invention can replace carbon black, which is beneficial to improving the laser transmittance of the material.
[0027] In the present invention, colorants of different colors are compounded to obtain a black colorant; the black colorant formed by colorants of different colors can replace carbon black, and the mass ratio of colorants of different colors can be adjusted. The compounding of two colorants is 1:(0.5-1.5); the compounding of three colorants is 1:(0.5-1.5):(0.5-1.5), and so on; wherein the specific value in (0.5-1.5) can be, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, etc.
[0028] As a preferred technical solution of the present invention, the nylon 66 composite material includes, by weight, 40 to 50 parts of nylon 66 resin, 25 to 35 parts of flat glass fibers, 13 to 15 parts of halogen-free flame retardants, 7.5 to 10 parts of synergistic flame retardants and 0.1 to 1 part of colorants.
[0029] Preferably, the nylon 66 composite material further includes 0 to 1.8 parts of other additives in parts by weight, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.8 parts, etc.
[0030] Preferably, the other auxiliary agents include at least one of an antioxidant, a light stabilizer, a lubricant, a release agent or an antistatic agent.
[0031] In the present invention, there is no excessive limitation on the types of auxiliary agents, and conventional auxiliary agents can be used. For example, the antioxidant includes but is not limited to any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 1098, or antioxidant DLTP.
[0032] The light stabilizer includes but is not limited to at least one of a hindered amine light stabilizer (such as light stabilizer 770, light stabilizer 622, light stabilizer 944, etc.), a benzophenone light stabilizer (such as UV531) or a benzotriazole light stabilizer.
[0033] The lubricant includes but is not limited to at least one of esters (such as polyethylene glycol esters, polyol esters), montanate, ethylene bisstearamide or polyethylene wax.
[0034] The release agent includes at least one of an inorganic release agent (such as talcum powder, mica powder, clay, etc.), an organic release agent (such as fatty acid, paraffin, glycerin, vaseline, etc.) or a polymer release agent (such as silicone oil, polyethylene glycol, low molecular weight polyethylene, etc.).
[0035] The antistatic agent includes at least one of a cationic antistatic agent (such as a quaternary ammonium salt), an anionic antistatic agent (such as an alkyl sulfonate, a phosphate), an amphoteric antistatic agent (such as an amphoteric imidazoline compound), a nonionic antistatic agent (such as a hydroxyethyl alkylamine, a fatty amide, a polyoxyethylene, a polyol ester) or a polymer antistatic agent (such as a polyether).
[0036] In a second aspect, the present invention provides a method for preparing the nylon 66 composite material according to the first aspect, the preparation method comprising the following steps:
[0037] The nylon 66 resin, flat glass fiber, halogen-free flame retardant and synergistic flame retardant are mixed and extruded to obtain the nylon 66 composite material.
[0038] Preferably, the mixed material further comprises a colorant and / or other auxiliary agents.
[0039] Preferably, the preparation method comprises premixing nylon 66 resin with a synergistic flame retardant and an optional colorant and other additives to obtain a premix; mixing the premix with flat glass fiber and a halogen-free flame retardant, and extruding to obtain the black nylon 66 composite material.
[0040] Preferably, the extrusion temperature is 180-270°C, for example, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, etc.
[0041] In the present invention, the temperature refers to the temperature range of different intervals of the twin-screw extruder. Exemplarily, the twin-screw extruder is divided into a first interval (temperature of 180-220°C), a second interval (temperature of 260-270°C), a third interval (temperature of 250-260°C), a fourth interval (temperature of 240-250°C), a fifth interval (temperature of 230-240°C), a sixth interval (temperature of 230-240°C), a seventh interval (temperature of 230-240°C), an eighth interval (temperature of 230-240°C), a ninth interval (temperature of 250-260°C), and a tenth interval (temperature of 260-270°C).
[0042] In a third aspect, the present invention provides an electronic and electrical component that can be laser welded, wherein the material of the electronic and electrical component includes the nylon 66 composite material as described in the first aspect.
[0043] In the present invention, the electronic and electrical components include a high-voltage connector, a charging gun plug and socket, a controller housing, etc.
[0044] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The nylon 66 composite material provided by the present invention is compounded by a synergistic flame retardant of a specific composition and a specific type of halogen-free flame retardant (i.e., inorganic hypophosphite), flat glass fiber and nylon 66 of a specific viscosity, so that the nylon 66 composite material can have both high laser transmittance and excellent flame retardant performance, and is resistant to high temperature and high humidity, has no precipitation after long-term treatment under high temperature and high humidity, and has good stability; it avoids the problem of decreased laser transmittance and easy precipitation caused by the use of other compounded flame retardants, and is particularly suitable for electronic components prepared by laser welding technology; the flame retardant grade of the nylon 66 composite material reaches V-1 or above, the laser transmittance is ≥27%, and after being placed in a high temperature and high humidity box at 85°C and 85%RH for 1000h, there is little precipitation. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0048] The materials used in the present invention are as follows:
[0049] PA66 resin 1: PA66 EP-158, viscosity 2.8, Huafeng Group;
[0050] PA66 resin 2: PA66 EPR32, viscosity 3.2, Shenma Group;
[0051] Flat glass fiber: ECS301HP-3-M4, Chongqing Composite International, short side monofilament diameter 6-8μm, average profile ratio 4.0, length 3mm;
[0052] Round glass fiber: ECS10-3.0-568H, Jushi Group, single fiber diameter 10um;
[0053] Inorganic hypophosphite: inorganic aluminum hypophosphite 4138, Qingyuan Yicheng;
[0054] Inorganic hypophosphite: Inorganic calcium hypophosphite 4132, Qingyuan Yicheng;
[0055] Diethylaluminum hypophosphite: OP 1230, Clariant;
[0056] Non-cage polysiloxane flame retardant: Dow 43-821, Dow Corning;
[0057] Cage-type polysilsesquioxane POSS: octaphenyl POSS and dodecaphenyl POSS, Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0058] MPP: melamine polyphosphate, 3141, Budenheim;
[0059] MCA: melamine cyanurate, Shouguang Weidong;
[0060] Colorant 1: Anthraquinone blue L308, Shenzhen Dingtai;
[0061] Colorant 2: Solvent Orange H554, BASF;
[0062] Colorant 3, complex red R297, BASF;
[0063] Unless otherwise specified, the colorant used in all the embodiments and comparative examples of the present invention is a mixture of colorant 1, colorant 2 and colorant 3 in a weight ratio of 1:1:1;
[0064] Lubricant: Oxidized polyethylene wax. Unless otherwise specified, the lubricant used in all the examples and comparative examples of the present invention is oxidized polyethylene wax.
[0065] Examples 1 to 10
[0066] Embodiments 1 to 10 respectively provide a nylon 66 composite material, and the formula of the nylon 66 composite material is shown in Table 1 (parts by weight); the preparation method of the nylon 66 composite material comprises: adding PA66 resin, synergistic flame retardant, colorant and other additives into a high-speed mixer, stirring evenly to obtain a mixture; adding the mixture into a twin-screw extruder through a precision feeder, adding flat glass fiber and halogen-free flame retardant through different side feeding ports, extruding, cooling, drying, and pelletizing to obtain the nylon 66 composite material; wherein the temperature settings of different intervals of the twin-screw extruder are 180°C, 270°C, 260°C, 250°C, 240°C, 240°C, 240°C, 240°C, 260°C, and 270°C, respectively.
[0067] Table 1
[0068]
[0069] Comparative Examples 1 to 8
[0070] Comparative Examples 1 to 8 respectively provide a nylon 66 composite material, the formula of the nylon 66 composite material is shown in Table 2 (parts by weight); the preparation method of the nylon 66 composite material is the same as that of Examples 1 to 10.
[0071] Table 2
[0072]
[0073] Performance Testing
[0074] (1) Flame retardant properties: The nylon 66 composite materials provided in Examples 1 to 10 and Comparative Examples 1 to 8 were injection molded into dumbbell-shaped specimens of 127 mm×12.7 mm×1.6 mm, and a vertical burning test was performed according to UL 94;
[0075] (2) Laser transmittance: The nylon 66 composite materials provided in Examples 1 to 10 and Comparative Examples 1 to 8 were injection molded into 200 mm × 100 mm × 2 mm samples and tested using a near infrared spectrometer (wavelength 900-1700 nm, Ocean Optics NIRQuest spectrometer);
[0076] (3) Precipitation level: The nylon 66 composite materials provided in Examples 1 to 10 and Comparative Examples 1 to 8 were injection molded into 200 mm × 100 mm × 2 mm samples, placed in a high temperature and high humidity box at 85°C and 85% RH for 1000 h, and then observed whether there was white precipitate on the surface of the sample. The evaluation standard for precipitation is divided into 5 levels, as follows: 1, no precipitation; 2, a small amount of foreign matter precipitated, and the number is <5; 3, some foreign matter precipitated, and 5≤number<8; 4, more foreign matter precipitated, and 8≤number<15; 5, serious precipitation, the number of foreign matter ≥15.
[0077] The specific test results are shown in Table 3:
[0078] Table 3
[0079]
[0080]
[0081] As shown in Table 3, the nylon 66 composite material provided by the present invention is compounded with a synergistic flame retardant of a specific composition and an inorganic hypophosphite and flat glass fiber, so that the nylon 66 composite material can have both high laser transmittance and excellent flame retardant properties, and is resistant to high temperature and high humidity, and has no precipitation after long-term treatment at high temperature and high humidity, and has good stability; it avoids the disadvantages of reduced laser transmittance and easy precipitation caused by the use of other compound flame retardants, and even black nylon materials have high laser transmittance, and are particularly suitable for products prepared by laser welding process. As shown in Examples 1 to 10, the flame retardant grade of the nylon 66 composite material reaches V-1 level, and the laser transmittance is ≥27%. Further, the flame retardant grade of the nylon 66 composite material reaches V-0 level, and the laser transmittance is ≥30%. After being placed in a high temperature and high humidity box at 85°C and 85%RH for 1000h, there is little precipitation.
[0082] It can be seen from Examples 4 to 7 that within the preferred range of the mass ratio of non-cage polysiloxane to cage polysilsesquioxane, the material can have both high laser transmittance and excellent flame retardant properties.
[0083] From the comparison between Example 3 and Comparative Example 1, it can be seen that only inorganic hypophosphite is used. Although the transmittance is high and the precipitation is small, the flame retardant performance cannot meet the V-0 level requirement; from Comparative Example 2, it can be seen that the laser transmittance of the composite material is significantly improved by using flat glass fiber; from Comparative Examples 3-4 and 6-7, it can be seen that without using a synergistic flame retardant of a specific composition, the material cannot have the effects of high laser transmittance, excellent flame retardant performance and less precipitation.
[0084] In summary, the present invention uses inorganic hypophosphite to compound with non-cage polysiloxane and cage polysilsesquioxane, which has the characteristics of high flame retardant efficiency and less precipitation. At the same time, flat glass fiber is compounded with a colorant, so that the PA66 composite material also has good laser transmittance.
[0085] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A nylon 66 composite material, characterized in that: In parts by weight, the nylon 66 composite material comprises 25 to 62 parts of nylon 66 resin, 13 to 54 parts of flat glass fiber, 10 to 20 parts of halogen-free flame retardant and 5.5 to 10 parts of synergistic flame retardant; The halogen-free flame retardant is an inorganic hypophosphite; The synergistic flame retardant includes a combination of non-cage polysiloxane and cage polysilsesquioxane; The viscosity of the nylon 66 resin is less than or equal to 3.0; The mass ratio of the non-cage polysiloxane to the cage polysilsesquioxane is 1:(0.1-5.5); The non-cage polysiloxane includes branched polysiloxane or linear polysiloxane; The inorganic hypophosphite includes at least one of inorganic aluminum hypophosphite, inorganic zinc hypophosphite, and inorganic calcium hypophosphite; The viscosity of the nylon 66 resin is tested according to the FZ / T51004-2011 standard.
2. The nylon 66 composite material according to claim 1, characterized in that: The short side monofilament diameter of the flat glass fiber is 6-15 μm; and the average profile ratio of the flat glass fiber is 3-5.
3. The nylon 66 composite material according to claim 1, characterized in that: The inorganic hypophosphite is inorganic aluminum hypophosphite.
4. The nylon 66 composite material according to claim 1, characterized in that: The mass ratio of the non-cage polysiloxane to the cage polysilsesquioxane is 1:(1-4).
5. The nylon 66 composite material according to claim 1, characterized in that: The cage-type polysilsesquioxane includes dodecaphenyl cage-type polysilsesquioxane and / or octaphenyl cage-type polysilsesquioxane; and the non-cage-type polysiloxane includes branched phenyl silicone oil.
6. The nylon 66 composite material according to claim 1, characterized in that: In parts by weight, the nylon 66 composite material also includes 0.05 to 1.2 parts of a colorant; the colorant includes at least one of linear quinacridone red, naphthoxylum red, complex red, azo orange, azo complex yellow, anthraquinone violet, anthraquinone blue, phthalocyanine blue or phthalocyanine green.
7. The nylon 66 composite material according to claim 1, characterized in that: In parts by weight, the nylon 66 composite material includes 40 to 50 parts of nylon 66 resin, 25 to 35 parts of flat glass fibers, 13 to 15 parts of halogen-free flame retardants, 7.5 to 10 parts of synergistic flame retardants and 0.1 to 1 part of colorants.
8. The nylon 66 composite material according to claim 1, characterized in that: The nylon 66 composite material further comprises 0 to 1.8 parts of other additives by weight; the other additives comprise at least one of an antioxidant, a light stabilizer, a lubricant, a release agent or an antistatic agent.
9. A method for preparing the nylon 66 composite material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: The nylon 66 resin, flat glass fiber, halogen-free flame retardant and synergistic flame retardant are mixed and extruded to obtain the nylon 66 composite material.
10. The preparation method according to claim 9, characterized in that: The mixed material also includes a colorant and / or other additives; the extrusion temperature is 180-270°C.
11. An electronic and electrical component capable of being welded by laser, characterized in that: The material of the electronic and electrical components includes the nylon 66 composite material as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of flame-retarding nylon 6 and uses thereof
CN105273182A
Halogen-free flame-retardant nylon composite material capable of being subjected to laser marking and preparation method thereof
CN113025035A